Is Prestige Only Beneficial? A Cost of Perceived External Prestige Among Accounting Employees. Issue 4 (7th August 2020) - Dalton, Derek W.; Vinson, Jeremy M.; Widener, Sally K.
Abstract: Perceived external prestige (PEP), which is an employee's belief of how outsiders view his or her organization, has a positive effect on multiple employee job outcomes. However, we posit that PEP also carries costs that arise due to increases in the perception of coworker competitiveness that negatively affects some job outcomes. Prior research has not yet examined negative outcomes of PEP. Using structural equation modeling with survey data from a sample of 477 accounting professionals employed in public accounting firms, we find that PEP is negatively related to job satisfaction and positively related to turnover intentions through its relationship with perceptions of the competitiveness of coworker environment, thus documenting a cost of PEP. Overall, though, we find that the net effect of PEP on job outcomes remains positive. Additionally, we find these relationships hold with 383 accounting professionals in industry. Implications for research and practice are discussed.